In Vitro Activities of Tigecycline against Erythromycin-Resistant Streptococcus pyogenes and Streptococcus agalactiae: Mechanisms of Macrolide and Tetracycline Resistance - Betriu, C. (American Society for Microbiology, 2004)
The activity of tigecycline was tested against erythromycin-resistant streptococci (107 Streptococcus pyogenes and 98 Streptococcus agalactiae strains). The presence of erythromycin and tetracycline resistance genes was determined by PCR. Among S. pyogenes strains the most prevalent gene was mef(A) (91.6%). The erm(B) gene was the most prevalent (65.3%) among S. agalactiae strains. Tigecycline proved to be very active against all the isolates tested (MIC at which 90% of the isolates tested were inhibited, 0.06 μg/ml), including those resistant to tetracycline.